MEMAHAMI PESAN AL-QUR'AN LEBIH DALAM: APLIKASI RETORIKA BALAGHAH UNTUK PENINGKATAN LITERASI KEAGAMAAN MASYARAKAT SEBUAH PENDEKATAN KONSEPTUAL - Muhammad Zul Fahmi; Muhammad Ihsan; Riska Handayani; Pandapotan Simbolon; Fitri Rahayu; Muhammad Hanafi; Fauziah Nur Ariza (LPPM STAI Muhammadiyah Probolinggo, 2025)
This article examines the role of balaghah (Arabic rhetoric) as a methodological approach to achieving a deeper and more contextual understanding of the Qur'an, and its contribution to enhancing religious literacy within Muslim communities. In Islamic tradition, balaghah consists of three primary branches—ma‘ānī (semantics), bayān (clarity through figurative language), and badī‘ (aesthetic embellishment)—which function to reveal the rhetorical power and layered meanings of the sacred text. Employing a qualitative-conceptual method based on literature review, this study analyzes both classical and contemporary sources, including peer-reviewed scholarly works. The findings demonstrate that integrating balaghah into Islamic education and da’wah practices can significantly improve critical and spiritual comprehension of the Qur’an, while countering rigid and literalist interpretations. Despite challenges such as the complexity of materials and lack of contextualized learning resources, pedagogical innovations—such as contextualized curriculum, digital media integration, and teacher training—offer promising solutions. Thus, balaghah is not only essential for understanding Qur'anic linguistic beauty, but also serves as a strategic tool for cultivating reflective, moderate, and textually literate Muslim communities. Keywords: Balaghah, Qur'anic Rhetoric, Religious Literacy, Tafsir, Islamic Education